Countermeasures of the Defence Forces of Ukraine against Means of Air Attack of the Russian Federation (February 24, 2022 — February 28, 2023) - Konopka, Volodymyr; Taranets, Sergii (Український історичний журнал, 2024)
The aims to trace the nature of the use of the air attack means (means of air attack include ballistic missiles, heavier-than-air aircrafts — military aircrafts, helicopters, cruise missiles, aerial bombs, UAVs, and aerostats) by the Russian Federation during the first year of the wide-scale invasion of the Russian Federation into Ukraine, based on the analysis and comparison and to determine the countermeasures and anti-aircraft means used by the Defence Forces of Ukraine.